A Comparison of Different Short-Term Macroeconomic Forecasting Models: Evidence from Armenia - Karen Poghosyan (Journal of Central Banking Theory and Practice, 2016)
We evaluate the forecasting performance of four competing models for short-term macroeconomic forecasting: the traditional VAR, small scale Bayesian VAR, Factor Augmented VAR and Bayesian Factor Augmented VAR models. Using Armenian quarterly actual macroeconomic time series from 1996Q1 – 2014Q4, we estimate parameters of four competing models. Based on the out-of-sample recursive forecast evaluations and using root mean squared error (RMSE) criterion we conclude that small scale Bayesian VAR and Bayesian Factor Augmented VAR models are more suitable for short-term forecasting than traditional unrestricted VAR model.
Keywords: C11; C13; C52; C53; 330; vector autoregression; Bayesian estimation; principal components; recursive regression; forecast evaluation; macroeconomic indicators; Armenia.